Breastfeeding and Neonatal Age Influence Neutrophil-Driven Ontogeny of Blood Cell Populations in the First Week of Human Life - Sebastiano Montante; Rym Ben-Othman; Nelly Amenyogbe; Asimenia Angelidou; Anita van den Biggelaar; Bing Cai; Yixuan Chen; Alansana Darboe; Joann Diray-Arce; Rebecca Ford; Olubukola Idoko; Amy Lee; et al. (Journal of Immunology Research)
The first few days of life are characterized by rapid external and internal changes that require substantial immune system adaptations. Despite growing evidence of the impact of this period on lifelong immune health, this period remains largely uncharted. To identify factors that may impact the trajectory of immune development, we conducted stringently standardized, high-throughput phenotyping of peripheral white blood cell (WBC) populations from 796 newborns across two distinct cohorts (The Gambia, West Africa; Papua New Guinea, Melanesia) in the framework of a Human Immunology Project Consortium (HIPC) study. Samples were collected twice from each newborn during the first week of life, first at Day of Life 0 (at birth) and then subsequently at Day of Life 1, 3, or 7 depending on the randomization group the newborn belongs to. The subsequent analysis was conducted at an unprecedented level of detail using flow cytometry and an unbiased automated gating algorithm. The results showed that WBC composition in peripheral blood changes along patterns highly conserved across populations and environments. Changes across days of life were most pronounced in the innate myeloid compartment. Breastfeeding, and at a smaller scale neonatal vaccination, were associated with changes in peripheral blood neutrophil and monocyte cell counts. Our results suggest a common trajectory of immune development in newborns and possible association with timing of breastfeeding initiation, which may contribute to immune-mediated protection from infection in early life. These data begin to outline a specific window of opportunity for interventions that could deliberately direct WBC composition, and with that, immune trajectory and thus ontogeny in early life. This trial is registered with NCT03246230.